Exploring Influence of Virtual Reality-Based English Learning Activities Towards Secondary Students’ English Writing Achievement - Sepang, Kevin Marion; Santosa, Made Hery; Suprianti, Gusti Ayu Putu (The Art of Teaching English as a Foreign Language (TATEFL), 2020)
The researcher conducted experimental research of using Virtual Reality as instructional media in form of Virtual Reality-based activities especially in learning English in form of writing skill. This research had two purposes, namely (1) to determine whether there is an effect of Virtual Reality-based English learning activities towards students’ English learning achievement in a public secondary school in North Bali, (2) to find out how VR-based English learning activities affects students’ English learning achievement in form of writing achievement. The research design used in this study was explanatory sequential explanatory mixed methods design. The population was first grade students of a public secondary school in North Bali. The result of qualitative data analysis showed that there is an effect of Virtual Reality-based English learning activities towards 10th grade students’ English learning achievement in public secondary school in North Bali. The Effect Size of this quantitative research is in range on low effect size. The result of qualitative data showed that there were strengths and weaknesses of using VR-based English learning activities that affects the result of quantitative data of the students’ English learning achievement in a public secondary school in North Bali in form of writing skill.